Analisis Kepuasan Pelanggan dalam Membeli Buah-buahan Segar di Moena Fresh Bali - PUTU OKA WARDIKA; RATNA KOMALA DEWI; NI WAYAN PUTU ARTINI (Agribusiness Study Program, Faculty of Agriculture, Udayana University, 2018)
Analysis Customer Satisfaction in Buying Fresh Fruits in Moena Fresh Bali Increased consumption of fruits in the country have an impact on the growth of fruitsales in Indonesia. This increase causes the appearance of stiff competition in thebusiness of fruits. Moena Fresh Bali as one of the companies that sell fresh fruitsmust innovate or improve the shortage so that the consumers do not turn to otherproducts. Consumer behavior may help explain how consumers obtain satisfaction.The purpose of this research is to determine satisfaction of Moena Fresh Baliconsumers and to find out actions to increase customer satisfaction of Moena Fresh.The location of the research was conducted at four Moena Fresh outlets as it wasconsidered to represent consumers in every sub-district in Denpasar City. Thenumber of respondents was as many as 50 respondents and the sampling wasconducted by using accidental sampling. Types of data collected include quantitativeand qualitative data which were sourced from primary and secondary data. Methodsof data collection were by using interview techniques, observation, anddocumentation. Data analysis methods used were descriptive analysis, ImportancePerformance Analysis and Customer Satisfaction Index. Based on the results ofresearch, the calculation of CSI to the attributes of Moena Fresh Bali was 77.6% i.e.it meets the criteria of satisfaction. Based on the Matrix of Importance Performance,product attributes are classified into four quadrants and actions to improve customersatisfaction are through the improvement of attributes that become the main priority,namely the attributes of advertising / promotion, price, and discounts. The studysuggests that Moena Fresh Bali should perform printed and electronic publicationsand set competitive prices to maintain its customers.